2007
DOI: 10.1371/journal.pgen.0030124
|View full text |Cite
|
Sign up to set email alerts
|

Complex Seizure Disorder Caused by Brunol4 Deficiency in Mice

Abstract: Idiopathic epilepsy is a common human disorder with a strong genetic component, usually exhibiting complex inheritance. We describe a new mouse mutation in C57BL/6J mice, called frequent-flyer (Ff), in which disruption of the gene encoding RNA-binding protein Bruno-like 4 (Brunol4) leads to limbic and severe tonic–clonic seizures in heterozygous mutants beginning in their third month. Younger heterozygous adults have a reduced seizure threshold. Although homozygotes do not survive well on the C57BL/6J backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 40 publications
5
75
1
Order By: Relevance
“…This gene belongs to a family of RNA-binding proteins involved in multiple aspects of RNA processing. 53 Its function in hematopoietic cells, however, has not been studied. Eleven other amplicons were found that occurred in less than 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…This gene belongs to a family of RNA-binding proteins involved in multiple aspects of RNA processing. 53 Its function in hematopoietic cells, however, has not been studied. Eleven other amplicons were found that occurred in less than 5% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Biol. 54: 209-214 (2010) expressed in the brain (Good et al, 2000;Ladd et al, 2001;Yang et al, 2007) with Brunol6 also in the kidney and testis . In chicken, 5 Brunol genes have been isolated, with Brunol1 (CELF3) missing.…”
Section: Abstract: Brunol Celf Xenopus Expression Patternmentioning
confidence: 99%
“…The RRMs confer RNA binding activity, and it is postulated that the divergent linker domain is an important site for functional regulation. Six members of the CELF family have been identified in humans and mice: CELF1 (CUGBP1) and CELF2 (CUGBP2) proteins are expressed ubiquitously and play vital role in embryogenesis [35], [36], [37], [38], [39], whereas CELF proteins 3-6 are restricted to adult tissues and found almost exclusively in the nervous system [40], [41]. CELF proteins often serve multiple functions in both the cytoplasm and the nucleus [42], [43].…”
Section: Evolutionary Conservation Of Celf Proteinsmentioning
confidence: 99%